Synthesis and Characterization of Thiophene Containing Bismaleimide and Polyaspartimides - Sivasankari, R.; Govindaraj, B.; Sarojadevi, M. (Asian Journal of Chemistry, 2012)
New class of aromatic bismaleimide containing thiophene ring were synthesized from bis-[(4-aminophenoxy)-6-naphthalene]-3-methyl-2-thiophenyl methane (BANTM) and maleic anhydride via bismaleamic acid as the intermediate followed by cyclodehydration. The structure of the monomers was confirmed by FTIR, 1H NMR and 13C NMR. Further, a series of polyaspartimides were synthesized by addition reaction of bismaleimide with various diamines. The polymers were characterized by FTIR, 1H NMR and 13C NMR. The polymers exhibit good solubility in organic solvents such as NMP, DMF and DMSO. The Tg and T10 % of the polyaspartimides are in the range of 199-212 ºC and 379-487 ºC respectively.